2021
DOI: 10.1186/s13054-021-03797-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the head-up position on cardiopulmonary resuscitation: a systematic review and meta-analysis

Abstract: Objective Experimental studies of head-up positioning (HUP) during cardiopulmonary resuscitation (CPR) have had some degree of conflicting published results. The current study aim was to analyze and reconcile those discrepancies in order to better clarify the effects of HUP CPR compared to conventional supine (SUP) CPR. Methods Three databases (PubMed, EMBASE and Cochrane Library) were searched comprehensively (from each respective database's ince… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 49 publications
1
6
0
1
Order By: Relevance
“…This study provides strong evidence that, compared with traditional closed-chest manual CPR performed in the supine/horizontal plane, OHCA patients with NS presentations can now have far higher likelihoods of SURV when treated by first-in responders who can amplify the lifesaving effects of C-CPR with rapid deployment of AHUP-CPR. These results confirm recent investigational breakthroughs in understanding the pivotal, synergistic role that gradual head/thorax elevation can play when combined with ITD/ACD-CPR (15, 17–23, 30–33).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This study provides strong evidence that, compared with traditional closed-chest manual CPR performed in the supine/horizontal plane, OHCA patients with NS presentations can now have far higher likelihoods of SURV when treated by first-in responders who can amplify the lifesaving effects of C-CPR with rapid deployment of AHUP-CPR. These results confirm recent investigational breakthroughs in understanding the pivotal, synergistic role that gradual head/thorax elevation can play when combined with ITD/ACD-CPR (15, 17–23, 30–33).…”
Section: Discussionsupporting
confidence: 86%
“…More recently, a comprehensive series of porcine ventricular fibrillation models identified a well-defined sequencing of interventions in which C-CPR is followed rapidly by ITD/ACD-CPR for 2 minutes, and then gradual head and thorax elevation over another 2 minutes. This well-studied cadence consistently results in near-normalization of cerebral perfusion pressures and profound improvements in neurologically favorable survival (17,19,20,(29)(30)(31)(32)(33). The pivotal adjuncts used to generate these synergistic physiologic benefits, including an automated head/thorax-up positioning (AHUP) device (Fig.…”
mentioning
confidence: 99%
“…Another study confirmed two-fold higher cerebral blood flow in animals receiving ACD+ITD CPR with head and thorax elevation compared with ACD+ITD flat during a prolonged CPR period [7]. In a meta-analysis of 131 animals from 7 studies, compared with supine CPR, CerPP, and Coronary Perfusion Pressure (CoPP) were significantly higher, and ICP was significantly lower [8]. A human cadaver study additionally confirmed the significant reduction in ICP with HUP CPR [9].…”
Section: Preclinical Studiesmentioning
confidence: 81%
“…None of these animals had ROSC [10]. In a meta-analysis of animal HUP CPR, CerPP, CorPP, and MAP were all significantly higher in animals that had cardiocerebral priming versus studies that did not perform priming [8]. Physiologically, this makes sense; after a long no-flow time, immediate whole-body elevation may result in blood volume dumping into the lower extremities.…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…Furthermore, compression on the internal abdominal organs, such as the liver, could push the blood in these organs into the inferior vena cava, increasing blood flow back to the heart (7). Previous clinical studies (28,29) have reported that STD-CPR can only provide approximately 20% to 30% of prearrest cardiac output, even when optimally performed. However, effective AACD-CPR could result in a maximum cardiac output of approximately 6 L/min (7,30), which is far beyond that of STD-CPR (1.5-3 L/min) (31).…”
Section: Discussionmentioning
confidence: 99%